2015
DOI: 10.4103/0970-9185.155152
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dexmedetomidine-propofol versus fentanyl-propofol for insertion of laryngeal mask airway

Abstract: Background and aims:Laryngeal mask airway (LMA) insertion requires anesthesia and suppression of airway reflexes. In search of an optimal drug, we compared dexmedetomidine and fentanyl, in combination with propofol for insertion of LMA.Material and Methods:This study was a prospective double blind randomized study. Eighty patients of ASA class 1&2 were randomly divided into two groups of 40 each. Group D received dexmedetomidine 1 mcg/kg and group F received fentanyl 1 mcg/kg intravenously (IV) over 2 minutes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 16 publications
(29 reference statements)
1
21
1
Order By: Relevance
“…Numerous agents have been studied and are still being studied to aid propofol in LMA insertion. These include drugs such as midazolam,[ 6 9 ] opioids such as fentanyl,[ 10 ] alfentanil,[ 11 12 ] remifentanil,[ 2 13 ] and butorphanol,[ 14 ] muscle relaxants such as mivacurium,[ 15 ] atracurium,[ 16 ] and rocuronium,[ 17 ] and drugs such as clonidine,[ 18 ] dexmedetomidine,[ 19 20 ] ketamine,[ 9 21 22 ] and lignocaine. [ 21 ] Side effects such as sedation, postoperative nausea, and vomiting, residual neuromuscular blockade, and cost remains a concern with these drugs, especially in the day care setting.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous agents have been studied and are still being studied to aid propofol in LMA insertion. These include drugs such as midazolam,[ 6 9 ] opioids such as fentanyl,[ 10 ] alfentanil,[ 11 12 ] remifentanil,[ 2 13 ] and butorphanol,[ 14 ] muscle relaxants such as mivacurium,[ 15 ] atracurium,[ 16 ] and rocuronium,[ 17 ] and drugs such as clonidine,[ 18 ] dexmedetomidine,[ 19 20 ] ketamine,[ 9 21 22 ] and lignocaine. [ 21 ] Side effects such as sedation, postoperative nausea, and vomiting, residual neuromuscular blockade, and cost remains a concern with these drugs, especially in the day care setting.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that dexmedetomidine and fentanyl in a dose of 1 μg/kg are equally effective and safe adjuvants for insertion of CLMA. [67] However we found very few studies comparing the efficacy of these commonly used adjuvants for PLMA insertion which requires greater depth of anesthesia. The primary objective of our study was to compare the effects of single intravenous dose of dexmedetomidine and fentanyl administered prior to propofol on the PLMA insertion conditions as per the Muzi scoring system.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, propofol as a sole anesthetic agent is unsatisfactory, and therefore, drugs such as opioids,[ 7 ] midazolam, ketamine, inhalational anesthetics, or muscle relaxants are used with propofol to decrease its dose and minimize undesirable effects. In addition, the use of muscle relaxants mandates that the patient be placed on mechanical ventilatory support, creating further stress on the pulmonary system.…”
Section: Introductionmentioning
confidence: 99%